PENGARUH AKTIVITAS FISIK JALAN PAGI TERHADAP TEKANAN DARAH PADA LANSIA DENGAN PENYAKIT HIPERTENSI DI UPT PSTW KHUSNUL KHOTIMAH PEKANBARU - Endi Supriyanto (Ensiklopedia of Journal, 2019)
The existence of an aging process that occurs in the elderly affects physiological changes and more and more diseases that arise and often suffer in the elderly. In old age there will be various setbacks in the organs of the body, therefore, the elderly are prone to diseases such as hypertension. The purpose of the study was to measure the effect of physical activity on the morning path to blood pressure in the elderly with hypertension at UPT PSTW Khusnul Khotimah Pekanbaru. This study uses a quasi-experimental method, with non-equivalent control group design. Sampling with purposive sampling technique and obtained 30 respondents. Data analysis using Shapiro Wilk and Paired T-test. The results of this study indicate the influence of physical activity on the morning path to blood pressure in the elderly with hypertension at UPT PSTW Khusnul Khotimah Pekanbaru. The results of statistical analysis Paired T-test P-value value 0,000 at pretest and posttest systole and 0.001 diastol pretest and posttest showed that Ha was accepted and Ho was rejected which meant that there was an effect of physical activity on the morning walk to blood pressure in the elderly. There is an effect on the physical activity of the morning road to blood pressure in the elderly with hypertension at UPT PSTW Khusnul Khotimah Pekanbaru. As a simple form of intervention to control blood pressure becomes stable.